Swaziland : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In Swaziland, government tax revenue has remained broadly stable over the past decade at a level slightly below 30 percent of gross domestic product. The sources of tax revenue are heavily concentrated, with customs receipts based on a revenue-sharing arrangement under the Southern African Customs Union (SACU) alone contributing more than one-half of total tax revenue, and company and personal income taxes (some 30 percent of tax revenue) and sales tax receipts (another 13 percent) accounting for the bulk of the remainder.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet